Emerging technologies, markets and commercialization of solid‐electrolytic hydrogen production. Issue 3 (2nd March 2018) - Badwal, Sukhvinder P.S.; Giddey, Sarbjit; Munnings, Christopher
Abstract : Around 60 million tons of hydrogen are generated globally each year, 96% of which is produced from fossil fuels. Very little hydrogen is used as energy media; instead, it is most commonly used in nonenergy‐related applications, such as the production of ammonia, fertilizer, methanol and other chemicals, the petrochemical industry, and the hydrogenation of products. However, there is a clear global shift in the use of hydrogen, which is now rapidly developing as a renewable fuel for both stationary and transport applications. Hydrogen can be transported in compressed form at high pressures, in liquid form at –253°C, or more conveniently converted to liquid fuels for easy transportation from locations high in renewable‐energy intensity to areas scarce in renewable resources. In the last 5 years there has been a significant advancement in the scale of solid‐electrolyte demonstrations with a number of megawatt (MW) class products under operation for onsite hydrogen generation, power to gas networks, and storage at multiple sites. This manuscript, building on our previous WIRES publication, discusses the commercialization status of renewable hydrogen‐generation technologies, along with advances in research and development linked to electrolytic hydrogen generation, use, and transportation in the form of liquid fuels such as ammonia, methanol, or dimethyl ether. This article is categorized under: Fuel Cells and Hydrogen > Science and Materials Fuel Cells and Hydrogen > Systems and Infrastructure Abstract : Renewable hydrogen and liquid fuels production with solid‐electrolytic technologies.